Faktor-faktor yang Mempengaruhi Kinerja Pemasaran Bank Perkreditan Rakyat - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
This research examined a marketing performance research model at BPR in the Special Territory of Yogyakarta caused by several predictor factors. Factors causing marketing performance constitute simultaneous predictor variables. These factors include skills, resources, values, uniqueness, perception of interest rate, customer satisfaction, customer loyality, and marketing performance.The result of significance test often hypotheses proposed in this research showed eight hypotheses were supported, while the other two hypotheses were not. The results of analysis employing AMOS program showed that the research model examined has not been accepted yet. This research involved just only two BPRs in the Special Territory of Yogyakarta. In order to get more varied and comprehensive data, future research needs to extend the number of data location.